Effect of intense swimming training on rhinitis in high-level competitive swimmers - Bougault, V.; Turmel, J.; Boulet, L. P. (Clinical & Experimental Allergy, 2010)
Summary Background Rhinitis is commonly reported by swimmers. Seasonal allergic rhinitis may impair athletes' performance and quality of life (QOL). No data are currently available on the changes of nasal symptoms during and after a swimming season. We aimed to determine in competitive swimmers: (1) the prevalence of rhinitis and its impact on their QOL during an intense training programme, (2) the changes in nasal symptoms and QOL after a resting period and (3) the relationship between rhinitis and airway hyperresponsiveness (AHR). Methods Thirty-nine swimmers and 30 healthy controls answered the Rhinitis Quality of Life Questionnaire (RQLQ) and scored nasal symptoms on a seven-point Likert scale during the week preceding their visit. Subjects had allergy skin prick tests and a methacholine challenge. Peak nasal inspiratory flows were also measured. The athletes performed these tests during an intense training period (V1), outside the pollen season and after at least 2 weeks without swimming (V2). Results At V1, rhinitis symptoms were reported by 74% of swimmers and 40% of controls (P<0.01). Eighty-four percent of swimmers and 72% of controls were atopic (NS). RQLQ score was higher in swimmers compared with controls at V1 (27.3 +/- 28.5 vs. 9.5 +/- 12.7, respectively, P<0.005). The presence of AHR during training did not correlate with the presence of rhinitis symptoms. At V2, the nasal symptoms and RQLQ scores were similar in swimmers and controls. Conclusion Intense swimming training is associated with an increase in nasal symptoms and impairment in QOL in most competitive swimmers. Such an increase is not related to seasonal allergen exposure in atopic athletes and probably results from chlorine derivative exposure.